UJI EFEKTIFITAS DAYA ANTELMINTIK INFUS DAUN KETEPENG CINA (Cassia alata L.) TERHADAP CACING GELANG (Ascaris lumbricoides) SECARA IN VITRO - lasut, Virginia; yamlean, Paulina; Supriati, Hamidah (UNIVERSITAS SAM RATULANGI, 2012)
ABSTRACTSuffer from worms is a chronic and endemic disease caused by parasite worm in high prevalence, notdeadly, but gnaw the health of the people therefore decrease the nutrient. The purposes of thisresearch are to know the effect of anthelmintic from infusion Ketepeng Chinese leaf (Cassia alata L.)toward Roundworms (Ascaris lumbricoides) and to know the effectiveness of infusion KetepengChinese leaf (Cassia alata L.) to get the anthelmintic effect toward Roundworms (Ascarislumbricoides). This research, used experiment method in order to know the anthelmintic effectinfusion Ketepeng Chinese leaf (Cassia alata L.) by 20%, 40% and 80% concentration in comparisonwith pirantel pamoate solution (combantrinÂ®) as a positive control and NaCl solution 0,9% asnegative control. The result of the research can showed that infusion Ketepeng Chinese leaf (Cassiaalata L.) by 20%, 40% and 80% concentration is proved to gave anthelmintic effect towardRoundworms (Ascaris lumbricoides) which get paralysis after 24 hours observation. Effective valuefrom infusion Ketepeng Chinese leaf (Cassia alata L.) which gives anthelmintic effect toward2Roundworms (Ascaris lumbricoides) is in 20% concentration. This concentration shows thatRoundworms gets paralysis, which is at 12th up to 18th hour, after being given treatment the wormsmovement is getting low and becoming slow and at the 24th hour Roundworms (Ascaris lumbricoides)gets paralysis, but it take much longer times than the concentration of 80% that have shownanthelmintic effects at the 12th hour.Keyword : Infusion, Ketepeng Chinese Leaf (Cassia alata L.), Anthelmintic Effect.